Effects of dexamethasone with sodium chloride load on the nitrite anion content in the rat’s blood serum, heart atria and ventricles - Sverediuk, Yu. A. (Journal of Education, Health and Sport, 2020)
The consequence of prolonged treatment with corticosteroids is development of hypertension and metabolic disorders. On the other hand, high levels of sodium chloride in the diet is able to amplify their risks. In a result of that disorders may be development metabolic cardiomyopathy. One of mechanisms that is capable to preventing hypertension and metabolic disorders is nitric oxide system. The research of that system, account short lifetime of the nitric oxide and features its metabolism, can be performed by analysis of nitrite anion (NO2-). It is mainly inactive metabolites in a result of the molecules NO. L-carnitine, as an antioxidant and having the ability to influence to energic metabolism, apoptosis and transcription of DNA may be a promising means for correction disorders in the nitric oxide system. The purpose of our study was to investigate the NO2- levels in the animals serum and heart tissue of both sex for long-term action of dexamethasone in conditions of high concentration of 4 % solution sodium chloride in water and use L-carnitine in order to correction data. The experiment was performed with the use of 96 mature white nonlinear rats. It was established that long-term use and high salt content and especially their combination conduced reduce of the NO2- level in the serum and ventricular myocardium. The high changes dominanced in the males. L-carnitine demonstrates the ability to recover the metabolite level. The characterised changes occur between both sex in animals with intake of usual quantity sodium chloride in water. The usage water with high content of sodium chloride caused more intensive negative changes but the difference between the sex was not as pronounced. The difference of content NO2- in the atria was found only between males and females. The dexamethasone or sodium chloride didn’t exert influence of the NO2- metabolism in that tissue.